2015
DOI: 10.1111/cmi.12445
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the host innate immune and inflammatory response by translocated bacterial proteins

Abstract: Summary Bacterial secretion systems play a central role in interfering with host inflammatory responses to promote replication in tissue sites. Many intracellular bacteria utilize secretion systems to promote their uptake and survival within host cells. An intracellular niche can help bacteria avoid killing by phagocytic cells, and may limit host sensing of bacterial components. Secretion systems can also play an important role in limiting host sensing of bacteria, by translocating proteins that disrupt host i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 109 publications
1
41
0
Order By: Relevance
“…Our new immunoblot data indicate that the previously observed effect of T2S on cytokine gene transcription (16) is due, at least partly, to a dampening of the macrophage's MAPK and NF-B pathways. Although it is possible that proteins secreted via T2S act directly on components of the MAPK and NF-B pathways, as has been documented following exposure to various pathogens (21,(74)(75)(76), we focused this study on discerning whether T2S diminishes the upstream event of PAMP recognition. By generating a set of human knockdown cell lines, we determined that the NLR, RLR, TRIF, and PKR pathways as well as ASC-and caspase-4-dependent inflammasomes are not required for the T2S dampening effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our new immunoblot data indicate that the previously observed effect of T2S on cytokine gene transcription (16) is due, at least partly, to a dampening of the macrophage's MAPK and NF-B pathways. Although it is possible that proteins secreted via T2S act directly on components of the MAPK and NF-B pathways, as has been documented following exposure to various pathogens (21,(74)(75)(76), we focused this study on discerning whether T2S diminishes the upstream event of PAMP recognition. By generating a set of human knockdown cell lines, we determined that the NLR, RLR, TRIF, and PKR pathways as well as ASC-and caspase-4-dependent inflammasomes are not required for the T2S dampening effect.…”
Section: Discussionmentioning
confidence: 99%
“…As is often the case with bacterial infections, this process is initiated in part by the recognition of pathogen-associated molecular patterns (PAMPs) by host surface or endosomal Toll-like receptors (TLRs), cytosolic nucleotide binding oligomerization domain (NOD)-like receptors (NLRs), retinoic acid-inducible protein I (RIG-I)-like receptors (RLRs), and inflammasomes (21)(22)(23). Upon PAMP recognition, signal transduction events activate the nuclear factor kappa B (NF-B) and mitogenactivated protein kinase (MAPK) pathways, causing the transcriptional activators NF-B and activator protein 1 (AP-1) to induce cytokine gene transcription (23).…”
mentioning
confidence: 99%
“…Successful bacterial pathogens have thus evolved strategies to mask these virulence factors from detection or to blunt the host response that is initiated (72)(73)(74). Indeed, a number of studies in several different systems have revealed that immune sensing of virulence factor activity promotes pathogen clearance (36,(75)(76)(77)(78)(79).…”
Section: Discussionmentioning
confidence: 99%
“…These systems contribute in various ways to infection processes among clinically-important pathogens, including Helicobacter pylori , Brucella and Bartonella species, Bordetella pertussis and Legionella pneumophila (13). The list of pathogens employing T4SSs to subvert host cellular pathways for establishment of a replication niche continues to expand, making these machines an important subject of study for defining critical features of disease progression and development of strategies aimed at suppressing T4SS function (4).…”
Section: Introductionmentioning
confidence: 99%
“…1). Upon translocation, the effector proteins target specific physiological pathways or biochemical processes with a variety of biological consequences that benefit survival, colonization, and transmission of the invading pathogens (3, 11, 12). …”
Section: Introductionmentioning
confidence: 99%